Transarterial chemoembolization as an alternative to radioembolization is associated with earlier tumor recurrence than in radioembolization-eligible patients - Chung, Sung Won; Cho, Heejin; Shin, Hyunjae; Park, Jeayeon; Kim, Ju Yeon; Hong, Ji Hoon; Hur, Moon Haeng; Park, Min Kyung; Lee, Yun Bin; Yu, Su Jong; Lee, Myungsu; Kim, Yoon Jun; et al. (Frontiers in Oncology, 2023)
Although transarterial radioembolization (TARE) using yttrium-90 (90Y) is a treatment option for large hepatocellular carcinoma (HCC), a fraction of patients are ineligible for TARE due to high lung shunt fraction (LSF). We evaluated if treatment with transarterial chemoembolization (TACE), owing to TARE ineligibility was associated with early HCC progression. Consecutive patients with HCC who were initially TARE candidates were included. Patients with vascular invasion or metastasis were excluded. Primary endpoints were time-to-progression (TTP) and overall survival (OS). The secondary endpoint was objective response rate. In total, 175 patients were included: 144 underwent TARE (TARE-eligible group) and 31 underwent TACE due to high LSF (TARE-ineligible group). This latter group had larger tumors (13.8 cm vs. 7.8 cm, P<0.001) and higher MoRAL scores (1,385.8 vs. 413.3, P=0.002) than the TARE-eligible group. After balancing baseline characteristics with an inverse probability of treatment weighting (IPTW), the TARE-ineligible group showed shorter TTP [adjusted hazard ratio (aHR)=2.16, 95% confidence interval (CI)=1.14¬¬–4.07, P=0.02] and OS (aHR=1.80, 95% CI=0.85¬¬–3.80, P=0.12), although the latter was not statistically significant. The TARE-ineligible group had a significantly lower objective response rate than the TARE-eligible group (9.7% vs. 56.9%, P<0.001). TARE-ineligible patients had larger tumors and higher MoRAL scores than TARE-eligible patients. Treatment with TACE, owing to high LSF, was associated with a shorter TTP even after balancing tumor size and MoRAL scores.